Modulatory Role of Simvastatin against Aluminium Chloride-Induced Behavioural and Biochemical Changes in Rats - Madhavan Nampoothiri; Jessy John; Nitesh Kumar; Jayesh Mudgal; Gopalan Kutty Nampurath; Mallikarjuna Rao Chamallamudi (Behavioural Neurology)
Objectives. Aluminium, a neurotoxic agent in humans, has been implicated in the pathogenesis of neurodegenerative disorders. In this study, we examined the behavioral and biochemical effects of aluminium in rats with special emphasis on memory centres, namely, hippocampus and frontal cortex. Further, the effect of simvastatin treatment on aluminium intoxication was evaluated. Methods. Rats were exposed to aluminium chloride (AlCl3) for 60 days. Simvastatin (10 mg/kg/p.o.) and rivastigmine (1 mg/kg/p.o.) were administered daily prior to AlCl3. Behavioral parameters were assessed using Morris water maze test and actophotometer followed by biochemical investigations, namely, acetylcholinesterase (AChE) activity, TNF-α level, antioxidant enzymes (GSH, catalase), lipid peroxidation, and nitrite level in hippocampus and frontal cortex. Triglycerides, total cholesterol, LDL, and HDL levels in serum were also determined. Key Findings. Simvastatin treatment improved cognitive function and locomotor activity in rats. Simvastatin reversed hyperlipidemia and significantly rectified the deleterious effect of AlCl3 on AChE activity. Further, in hippocampus and frontal cortex, aluminium-induced elevation in nitrite and TNF-α and reduction in antioxidant enzymes were inhibited by simvastatin. Conclusion. To conclude, the present study suggests that simvastatin per se protects the neurons in hippocampus and frontal cortex from AlCl3, an environmental toxin.